Public Service Innovations in China
XVII, 218 p. 7 illus., 3 illus. in color.
Keywords: This edited volume presents case studies of the transformation of China’s public services over the past decade in China. As the country has experienced fundamental changes in its demographic, economic, social and environmental structures, demands on public services have been increasing tremendously, and have become unprecedentedly diverse. In response, innovations to provide new services, expand service recipients, adopt new technologies, engage partners, and streamline service processes have been employed widely in China to increase service efficiency, enhance quality, enlarge coverage, and improve citizen satisfaction. This book examines prominent cases of public service innovations in China, disclosing their causes, patterns, diffusion, and effects. These cases provide interesting evidence about the nature and effectiveness of public service innovations in China while highlighting to what extent these innovations can be explained by accepted theories and whether new theory buildingis needed. This book will be of value to academics and policymakers seeking to understand the evolving Chinese political system. .